Safeguarding democratically elected local government councils in Nigeria from abuse - Aliyu, Musa Adamu; Abdullah, Anita; Mohd Anuar, Haslinda (Future Academy, 2018)
Nigeria is a country that practices constitutional democracy. The 1999 Constitution (As Amended) being a fundamental law, prevails over other inconsistent legislations. The country is a geographical entity divided into 36 states. Each of the states has a certain number of local government councils constitutionally provided. The Grundnorm makes it compulsory for the local government councils to be democratically governed. State Governments are empowered to ensure, there is a law in existence, to regulate the administrative and financial structure of the local government councils. The executive and legislature at the state level, have unfortunately devised a mode of circumventing the constitutional provisions which guaranteed democratically elected local government councils. It is the objective of this conceptual paper, to analyse the constitutional powers of the state governments to control the local government councils. The paper argues that the Code of Conduct Tribunal, being a quasi-adjudicatory body, has the power to sanction public officers who abuse their powers. Invoking the Tribunal’s jurisdiction by subjecting public officers to trial for the abuse will play a vital role in deterring the State Governors and Members of the State House of Assembly from the infraction of the constitutional provisions. This role will go a long way in safeguarding democratically elected local government councils as constitutionally guaranteed in Nigeria.